PELATIHAN DIVERSIFIKASI PRODUK OLAHAN IKAN BAGI PEREMPUAN PESISIR DI KABUPATEN LOMBOK TIMUR - Muslihuddin Aini; Zia Zannititah Pawana; Miftahurrizki Miftahurrizki (Universitas Mataram, 2023)
The impact of weather and climate causes uncertainty in fishing. This affects the income of small fishermen which has an impact on the welfare of fishermen's families. To overcome this, it is necessary to make efforts to create alternative livelihoods for small fishing families. One of the livelihoods that has the potential to be developed is the fishery product processing business. By targeting coastal women who come from fishing families, efforts are made to increase capacity in processing fishery products. The purpose of this activity is to increase the knowledge and skills of coastal women in East Lombok Regency in the field of processing fishery products; improving the economy of small fishing families in the Coastal District of East Lombok. In this activity, training on fish processing diversification was conducted for coastal women in East Lombok. The stages carried out in this service were a preliminary survey using observation and interview methods, while for training using lecture, discussion, question and answer and practice methods. The result of this service is that coastal women in East Lombok Regency have knowledge and skills in making fish-based processed products. The Poklahsar Keluarga Bahari and Poklahsar Selamat Hati in Sugian Village have the ability to make fish balls, fish brains and fish crackers. The Coastal Kitchen Poklahsar and the Pawon Mandar Poklahsar in Labuhan Haji Village have the ability to make fish sauce. Poklahsar Bujamatasa and Poklahsar Bunga Tanjoh in Tanjung Luar Village have the ability to make fish dimsum, fish nuggets and fish crackers. Further training is needed in the form of training on packaging, marketing, financial management, product legality, to business management and business evaluation.